Baby boomers can my eighties be like my fifties? - Mellor, M. Joanna; Rehr, Helen (Springer series on life styles and issues in aging., 2005)
"Based on a conference funded by the Robert Wood Johnson Foundation, this book brings together baby boomers and health care professionals to explore baby boomers' perceptions of their future social-health care expectations and needs"--Provided by publisher.